ผลการใช้ชุดกิจกรรมภาษาอังกฤษเสริมหลักสูตรนอกชั้นเรียนเรื่องวันหยุดนักขัตฤกษ์และเทศกาลสำคัญสำหรับใช้ในมุมภาษาอังกฤษที่มีต่อความสามารถในการสื่อสารภาษาอังกฤษ ความเข้าใจในวัฒนธรรม ทักษะสังคมและทัศนคติต่อภาษาอังกฤษของนักเรียนประถมศึกษา - มามาตร, กัญญาพัฒน์; โตรัตน์, บำรุง (วารสาร ศึกษาศาสตร์ มมร, 2020)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เพื่อศึกษา วิเคราะห์ข้อมูลพื้นฐานที่เกี่ยวข้องกับการจัดกิจกรรมภาษาอังกฤษเสริมหลักสูตรนอกชั้นเรียนระดับประถมศึกษาประกอบด้วยภูมิหลังทางภาษาของผู้เรียนด้านทักษะการฟัง – พูด ความรู้ความเข้าใจของผู้เรียนด้านวัฒนธรรมเจ้าของภาษาเกี่ยวกับวันหยุดนักขัตฤกษ์และเทศกาลสำคัญ และองค์ประกอบทั่วไปที่ส่งเสริมการเรียนรู้ภาษาอังกฤษนอกชั้นเรียน 2) เพื่อพัฒนาและหาประสิทธิภาพของชุดกิจกรรมฯ ให้มีประสิทธิภาพตามเกณฑ์ 75/75 และ 3) เพื่อประเมินประสิทธิผลการใช้ชุดกิจกรรมด้านผลความสามารถในการสื่อสารภาษาอังกฤษด้านการฟัง-พูด ความรู้ความเข้าใจด้านวัฒนธรรม  ทักษะสังคม ทัศนคติต่อภาษาอังกฤษและความพึงพอใจที่มีต่อชุดกิจกรรม  กลุ่มตัวอย่างการวิจัย คือ นักเรียนชั้นประถมศึกษาปีที่ 4-6 ปีการศึกษา 2561 จำนวน 30 คน โดยมาจากนักเรียนที่เลือกกิจกรรมชุมนุมภาษาอังกฤษโดยสมัครใจ ซึ่งนักเรียนทุกคนมีพื้นฐานการเรียนภาษาอังกฤษมาเป็นเวลา 6-9 ปี การวิเคราะห์ข้อมูลใช้ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าขนาดของผล (Effect size) และค่าสถิติทดสอบค่า t (Dependent t-test)             ผลการวิจัยพบว่า   นักเรียนชั้นประถมมีความรู้พื้นฐานเกี่ยวกับความสามารถในการฟังภาพรวมอยู่ในระดับน้อย อีกทั้งความรู้พื้นฐานเกี่ยวกับความสามารถในการสื่อสารภาษาอังกฤษด้านการพูด ควรพัฒนาการสื่อสารโต้ตอบในบทสนทนาที่เกี่ยวกับเรื่องราวใกล้ตัวหรือเรื่องราวที่เรียนรู้เพิ่มเติม รวมถึงการนำเสนอ การรายงานข้อมูลที่ค้นคว้าเป็นภาษาอังกฤษได้ ชุดกิจกรรมที่สร้างขึ้น มีประสิทธิภาพอยู่ในเกณฑ์ระดับดี มีค่าประสิทธิภาพ E 1 /E 2 เท่ากับ50/80.17 ผลการประเมินประสิทธิผลหลังเรียนใช้ชุดกิจกรรม มีดังนี้ นักเรียนมีความสามารถในการสื่อสารภาษาอังกฤษเน้นทักษะการฟัง-พูดหลังเรียนด้วยชุดกิจกรรมฯสูงกว่าก่อนเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และผลมีขนาดใหญ่มาก นักเรียนมีความรู้ความเข้าใจหลังเรียนด้วยชุดกิจกรรมฯ สูงกว่าก่อนเรียน อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และผลมีขนาดใหญ่มาก นักเรียนมีพฤติกรรมด้านทักษะสังคมหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ.05 และมีผลขนาดใหญ่มาก นักเรียน มีทัศนคติต่อภาษาอังกฤษอยู่ในระดับดีและสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 นักเรียนมีความพึงพอใจต่อชุดกิจกรรมภาษาอังกฤษเสริมหลักสูตรนอกชั้นเรียนเรื่องวันหยุดนักขัตฤกษ์และเทศกาลสำคัญอยู่ในระดับพึงพอใจมาก   The objectives were 1) to study and analyze the students’ information about English extra curriculum activities, which consisted of students’ background of listening and speaking skills, cultural understanding about holidays and festivals, and others factors that supported extra curriculum activities, 2) to develop an English Extra Curriculum Package focusing on Holidays and Festivals for English corners to meet the efficiency criteria of E1/E2 = 75/75, which compare the percentage averages of the formative assessment scores with the summative assessment scores, and 3) to investigate the effectiveness of the English Extra Curriculum Package focusing on Holidays and Festivals for use in English corners by comparing communicative abilities focusing on listening and speaking skills, cultural understanding, social skills behaviors, Student’s English language attitudes before and after using the package and its effect size, and students’ satisfaction after using package. The sample was 30 elementary students (grade 4-6) that joined in English club in academic year 2018 by volunteering. Data were collected and analyzed by mean, standard deviation, t-test (dependent t-test), and effect size. The research findings were as follows: 1) The students’ information about English extra curriculum activities were identified. Students’ background of listening and speaking skills were at average level, cultural understanding about holidays and festivals, and others factors that supported extra curriculum activities 2) The developed English Extra Curriculum Package reached the efficiency by comparing the percentage of formative assessment score (E1) =79.50 with summative assessment scores (E2) =80.17 After implementation of the English Extra Curriculum package, the learning evaluation revealed the following results: 1) The average scores of English communicative abilities focusing on listening and speaking skills of students in posttest were significantly higher than pretest scores at the .05 level and its effect size was very large. 2) The average scores of cultural understanding focusing on holidays and festivals of students in posttest were significantly higher than pretest scores at the .05 level and its effect size was very large. 3) The average scores of social skills behaviors of students in posttest were significantly higher than pretest scores at the .05 level and its effect size was very large. 4) The average scores of student’s language attitudes in posttest were at good level and significantly higher than pretest scores at the .05 level and its effect size was very large . 5) The satisfaction survey indicated that students’ overall satisfaction toward the English Extra Curriculum package was at the high level.